The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9091942
|View full text |Cite
|
Sign up to set email alerts
|

Y-Box Binding Protein 1 Expression in Trophoblast Cells Promotes Fetal and Placental Development

Abstract: Y-box binding protein 1 (YB-1) is pivotal for the regulation of cancerogenesis and inflammation. However, its involvement in pregnancy processes such as fetal and placental development remains to be elucidated. We studied Ybx1 (YB-1)+/− heterozygous intercrossings and compared them to YB-1+/+ wild-type (WT) combinations. Additionally, we generated trophoblast-specific YB-1-deficient mice by pairing FVB Cyp19-Cre females to YB-1fl/fl males. YB-1fl/fl-paired FVB WT females served as controls. Serial in vivo ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…During pregnancy, these processes are also crucial for the normal development of the placenta and changes in YB-1 expression might be involved in impaired placenta growth and/or functionality. We have recently shown that heterozygous YBX1 mice and mice with trophoblast-specific YBX1 deficiency display placental abnormalities with subsequent fetal growth retardation [20]. The present study demonstrates that pregnancy-associated disorders are associated with altered YB-1 concentrations in tissue and blood samples.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…During pregnancy, these processes are also crucial for the normal development of the placenta and changes in YB-1 expression might be involved in impaired placenta growth and/or functionality. We have recently shown that heterozygous YBX1 mice and mice with trophoblast-specific YBX1 deficiency display placental abnormalities with subsequent fetal growth retardation [20]. The present study demonstrates that pregnancy-associated disorders are associated with altered YB-1 concentrations in tissue and blood samples.…”
Section: Discussionsupporting
confidence: 63%
“…In YBX1-/-knockout embryos, the development advances usually up to embryonic day 10.5 (E10.5), and, afterwards, they exhibit severe growth retardation, neurological and pulmonary lesions, and are embryonically lethal by E18 [18,19], which indicates that YB-1 is necessary at late developmental stages. Recently, we characterized the effects of YB-1 deficiency on placenta development in vivo [20], where trophoblast-specific YB-1 deficient mice showed reduced implantation areas and negatively affected gross placental morphometry already at E10 [20]. This shows a direct involvement of YB-1 not only in placenta growth but also in implantation processes.…”
Section: Introductionmentioning
confidence: 92%
“…Our previous study has shown that maternal exposure to environmental pollutants DEHP during pregnancy induces fetal growth restriction by inhibiting the proliferation of placental cells through DNA damage [ 17 ]. Placental development defects are associated with fetal growth retardation, leading to adverse pregnancy outcomes and some diseases in adulthood of offsprings [ 39 , 40 ]. Therefore, it is very essential to understand the mechanism of DNA damage in placental cells treated by DEHP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fetal growth impairment, also the placenta showed certain functional and structural alterations in YB-1 deficiency. We have been able to show that IUGR might be a result of placenta insufficiency demonstrated by increased placental diameter/thickness ratio and weight at GD14 as well as inadequate SA remodeling in trophoblast-specific YB-1 deficient mice (Meyer et al, 2020). By overexpressing or downregulating YB-1 in two different trophoblast cell lines HTR8/SVneo and JEG3, we aimed to disclose the cellular mechanism underlying the placental dysfunction (Stojanovska et al, 2021).…”
Section: Yb-1 In Pregnancy and Related Disordersmentioning
confidence: 99%
“…Among the YB proteins, YB-1 seems to be developmentally most important: In comparison to the loss of YB-2 and YB-3, YB-1 is mostly embryonic lethal as demonstrated in YB-1 null mutant (YB1 −/− ) mice ( Lu et al, 2005 ; Uchiumi et al, 2006 ). However, the serious consequences of YB-1 deficiency become only evident after the first trimester, when a functional placenta is already established ( Meyer et al, 2020 ). This suggests that implantation and early decidualization are not dependent on YB-1 or that there are efficient compensatory mechanisms.…”
Section: Yb-1 In Pregnancy and Related Disordersmentioning
confidence: 99%